2019
DOI: 10.1002/ejic.201901035
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Lewis Acidic Sites in “TMA‐Free” Phenol‐Modified Methylaluminoxane

Abstract: “Structural” AlMe2(bht) was found to be an integral building block of the “TMA‐free” olefin polymerization cocatalyst MAO/BHT (TMA = trimethylaluminum, MAO = methylaluminoxane, BHT = 2,6‐di‐tert‐butyl‐4‐methylphenol). NMR studies show that treatment of MAO/BHT with the neutral N‐donor pyridine (py) leads to selective generation of neutral AlMe2(bht)(py). The reaction of MAO/BHT with 2,2'‐bipyridine (bipy) generates cationic [AlMe(bht)(bipy)]+ fragments (bht = BHT phenolate), analogously to what happens when un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 105 publications
0
36
0
Order By: Relevance
“…11,21,28,29 Ionization in MAO comes about via neutral MAO generating the reactive Lewis acidic species [Me 2 Al] + , with the resulting bulky MAO anions being sufficiently weakly coordinating to allow high reactivity towards alkenes at the cationic metal center. [30][31][32][33][34] We have shown through mass spectrometric means that the anionic products of the activation process are dominated by a single ion, [(MeAlO) 16 (Me 3 Al) 6 Me] À henceforth [16,6] À . 35 The three dimensional structure of this anion has not been elucidated, but its unusually high abundance in the spectra of postactivation commercial MAO does raise questions about why it is so prominent, since the synthesis of MAO does not on the face of it appear to be particularly selective, being the controlled mixing of water and pyrophoric TMA.…”
Section: Introductionmentioning
confidence: 99%
“…11,21,28,29 Ionization in MAO comes about via neutral MAO generating the reactive Lewis acidic species [Me 2 Al] + , with the resulting bulky MAO anions being sufficiently weakly coordinating to allow high reactivity towards alkenes at the cationic metal center. [30][31][32][33][34] We have shown through mass spectrometric means that the anionic products of the activation process are dominated by a single ion, [(MeAlO) 16 (Me 3 Al) 6 Me] À henceforth [16,6] À . 35 The three dimensional structure of this anion has not been elucidated, but its unusually high abundance in the spectra of postactivation commercial MAO does raise questions about why it is so prominent, since the synthesis of MAO does not on the face of it appear to be particularly selective, being the controlled mixing of water and pyrophoric TMA.…”
Section: Introductionmentioning
confidence: 99%
“…The computational protocol M06-2X/TZ(PCM)//TPSSTPSS/DZ has been previously benchmarked 56 , 57 and widely used for modeling of Al-species relevant to olefin polymerization 33 , 44 , 58 , 59 and other research fields, 60 and it has been shown to be suitable for studies related to MAO activators. 19 , 33 , 35 , 41 , 51 , 61 Additional inclusion of Grimme-type long-range dispersion corrections 62 , 63 does not affect computational results significantly (see Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…A Δ G R close to zero for this reaction is consistent with the experimental observation that ionization occurs with bipy but not py . 44 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations